Electrochemical Detection of Low-concentration Lead (II) Ions from Water - (:unkn) unknown (My University, 2017)
The aim of this study was to develop an electrochemical sensor for speedy, selective and sensitive detection of lead ion (Pb2+) using graphene oxide and pyrrole nanocomposite. Different combinations of graphene oxide and pyrrole in layers and mixtures were tested for the finest sensitive detection of lead ion (Pb2+). Reduced graphene oxide and polypyrrole (rGO-PPY as layer) nanocomposite modified screen printed electrode (SPE) showed the best signal in response to the differential pulse anodic stripping voltammetry (DPASV) with a limit of detection to 5 ppb. The rGO-PPY modified electrode possessed a large effective surface area because of the unique 3D porous architectures and displayed good selectivity for determination of Pb2+ in presence of Cu2+. The differential pulse anodic stripping voltammetry signals were analyzed and relevant parameters were optimized. The developed rGO-PPy nanocomposite modified SPE sensor was tested with the spiked tap water solution to validate its applicability in real sample analysis. The sensor structure and the fabrication method of the developed sensor is rapid and simple to follow compared to complex and time consuming electrochemical synthesis process. Moreover, this fabrication process can be easily modified and implemented using a printing device for inexpensive mass production.